CRITICAL DISCOURSE ANALYSIS OF GILLETTE® AUDIOVISUAL AD ENTITLED “WE BELIEVE: THE BEST MEN CAN BE” - Muftihaturrahmah Burhamzah; Alamsyah Alamsyah; Lely Novia (Universitas Lambung Mangkurat, 2021)
Advertising is one of the ways that can influence people to purchase products, services, or shaping one's mind for a way of life. The audiovisual ad gives more benefits over the audio one or the visual one because it is more attractive and can provide a clear view of the goods or the ideas by combining the audio and visual aspects. Bullying and sexual harassment have become a common issue that happened in society around the world. These issues give a negative impact on society, especially to the victims even to the men themselves. Gillette® had launched an audiovisual ad related to bullying and sexual harassment in 2019. The ad tries to convey the men to stop the bullying and sexual harassment issue caused by toxic masculinity happened worldwide. This study aims to critically study the text, the discursive practice, and the socio-cultural practice of the Gillette® audiovisual ad entitled “We Believe: The Best Man Can Be” by using the Fairclough’s method of Critical Discourse Analyses (CDA). From the textual analysis, it is found that the ad is using: (1) questioning form of sentences invoking the previous tagline of Gillette® “The Best a Man Can Get” to reinforce the campaign message of “The Best Man Can Be”; (2) using three kinds of tenses (present tense, future tense, and present perfect continues tense) in stating the fact related to toxic masculinity which has been going on far too long and also in saying the consequence of the ad's campaign message happened in the future; (3) using the pronoun